TO COMPARE THE EFFECTIVENESS OF USING ORAL PROPHYLACTIC ANTIBIOTICS WITH PARENTERAL PROPHYLACTIC ANTIBIOTICS IN ENDOVASCULAR INTERVENTION’S DIAGNOSIS AND TREATMENT (Vietnam Journal of Community Medicine, 2022)
Objective: To compare the effectiveness of using oral prophylactic antibiotics with parenteral prophylactic antibiotics in endovascular intervention’s diagnosis and treatment at 30/4 hospital – Ministry of Public Security. Subjects and methods: Prospective, cross-sectional and comparative study on 95 patients who received antibiotic prophylaxis when performing endovascular intervention’s diagnosis and treatment techniques at the Department of Interventional Cardiology, 30/4 hospital - Ministry of Public Security from June 2020 to June 2021. Results: There were no significant differences in body temperature, white blood cell count, erythrocyte sedimentation rate and elevated CRP rate in the two groups of patients (oral antibiotic group and parenteral antibiotic group). Conclusion: The effectiveness of oral prophylactic antibiotics was equivalent to that of parenteral antibiotic prophylaxis.
Keywords: Prophylactic antibiotics, endovascular intervention.